Cannabinoids as Glial Cell Modulators in Ischemic Stroke: Implications for Neuroprotection - Vicente-Acosta, Andrés; Ceprian, Maria; Sobrino, Pilar; Pazos, Maria Ruth; Loría, Frida (Frontiers in Pharmacology, 2022)
Stroke is the second leading cause of death worldwide following coronary heart disease. Despite significant efforts to find effective treatments to reduce neurological damage, many patients suffer from sequelae that impair their quality of life. For this reason, the search for new therapeutic options for the treatment of these patients is a priority. Glial cells, including microglia, astrocytes and oligodendrocytes, participate in crucial processes that allow the correct functioning of the neural tissue, being actively involved in the pathophysiological mechanisms of ischemic stroke. Although the exact mechanisms by which glial cells contribute in the pathophysiological context of stroke are not yet completely understood, they have emerged as potentially therapeutic targets to improve brain recovery. The endocannabinoid system (ECS) has interesting immunomodulatory and protective effects in glial cells, and the pharmacological modulation of this signaling pathway has revealed potential neuroprotective effects in different neurological diseases. Therefore, here we recapitulate current findings on the potential promising contribution of the ECS pharmacological manipulation in glial cells for the treatment of ischemic stroke.